Super-hydrophobic oleophylic cellulose composite aerogel material and preparation method thereof
By introducing SiO2 into the cellulose wet gel and performing hydrophobic modification, the problem of poor superhydrophobicity of cellulose aerogel is solved, and an efficient oil absorption and reusable superhydrophobic oleophilic cellulose composite aerogel material is achieved.
Patent Information
- Application Number
- CN202411789852.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-04
AI Technical Summary
Existing cellulose aerogel materials have poor superhydrophobic properties when dealing with oil stain adsorption, resulting in poor oil stain adsorption performance.
Superhydrophobic oleophilic cellulose composite aerogel is prepared by placing the cellulose wet gel in ethyl orthosilicate hydrolyzate hydrolyzate hydrolyzate hydrolyzed to alkaline, forming SiO2-reinforced cellulose composite aerogel, and subjecting hydrophobic modification in an alkyl siloxane solution.
The superhydrophobic properties of cellulose aerogel materials are achieved, with a water contact angle of 153-160° and a water droplet rolling angle of 2.9-5.8°. It also has excellent oil absorption performance, and the oil absorption efficiency is 11.5-13.2 times its own weight, and can be reused.
Smart Images

Figure CN119552415A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel materials, and in particular relates to a super hydrophobic and oleophilic cellulose composite aerogel material and a preparation method thereof. Background Art
[0002] In recent years, a large number of oil spills have posed a serious threat to fragile ecosystems. To deal with large-scale oil spills on the sea surface, it is usually first intercepted with oil booms, and then the oil is pumped away with skimmers, but in the end a small amount of oil will still remain on the sea surface. Therefore, the common recovery and cleaning method for thin oil layers and small oil layers on the sea surface is adsorption. Adsorption materials are usually natural materials, such as zeolite, bentonite, wool fiber, etc., but these adsorption materials have disadvantages such as high density, low absorption rate and poor oil-water selectivity, which limit their practical application. Therefore, new environmentally friendly materials with super hydrophobicity and super oleophilicity are in urgent need of development. As a new third-generation material, cellulose aerogel not only has the performance of traditional aerogel, but also has its own unique properties. Cellulose aerogel is rich in hydroxyl groups, has a large specific surface area and high porosity, and exhibits excellent water and oil absorption properties. However, cellulose aerogel materials have a large number of hydroxyl groups, which absorb water while absorbing oil. Cellulose needs to be modified in order to be better used to treat floating oil on the water surface. Nano-silicon dioxide (SiO2), high stability, low thermal conductivity, and rough surface characteristics make it a focus of attention in the research of super-hydrophobic surface preparation.
[0003] Some researchers have prepared cellulose / SiO2 composite aerogels by combining the characteristics of cellulose and SiO2. However, due to the structure and hydrophilicity of cellulose itself, the composite aerogels can only achieve hydrophobicity and lipophilicity. The static contact angle cannot be greater than 150° and the rolling angle cannot be less than 10°. The superhydrophobic performance requirements are not achieved, which greatly reduces the performance of cellulose aerogels in dealing with oil adsorption. Summary of the invention
[0004] The purpose of the present invention is to overcome the above technical deficiencies, provide a super hydrophobic and oleophilic cellulose composite aerogel material and a preparation method thereof, and solve the technical problem in the prior art that the cellulose aerogel has poor super hydrophobicity and leads to poor oil adsorption performance.
[0005] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a super hydrophobic and oleophilic cellulose composite aerogel material, comprising the following steps: S1, placing a cellulose wet gel in a ethyl orthosilicate hydrolyzate solution, and adjusting the pH value to alkaline, and obtaining a SiO2-reinforced cellulose composite aerogel through immersion treatment and drying treatment; S2, immersing the SiO2-reinforced cellulose composite aerogel in an alkyl siloxane solution for hydrophobic modification treatment, and drying to obtain a super hydrophobic and oleophilic cellulose composite aerogel material.
[0006] In a second aspect, the present invention provides a super hydrophobic oleophilic cellulose composite aerogel material obtained by the above preparation method, wherein the water contact angle of the super hydrophobic oleophilic cellulose composite aerogel material is 153-160°, and the rolling angle of water droplets on its surface is 2.9-5.8°.
[0007] Compared with the prior art, the present invention has the following beneficial effects: The present invention utilizes the large specific surface area, high porosity, and excellent water and oil absorption performance of cellulose aerogel, combined with highly stable nano-silica, to form a SiO2-reinforced cellulose composite aerogel with cellulose aerogel as the matrix and SiO2 particles as the reinforcing phase, and controls the pH in the reaction process to be alkaline, controls the hydrolysis-polycondensation rate of tetraethyl orthosilicate (TEOS), regulates the particle size and protrusion size of SiO2 particles, and realizes the composite of cellulose and SiO2 in this process, so as to appropriately improve the surface roughness of the cellulose aerogel, and then prepares a super-hydrophobic and oleophilic cellulose composite aerogel material after hydrophobic modification by alkylsiloxane. The super-hydrophobic and oleophilic cellulose composite aerogel of the present invention has a contact angle with water of 153-160°, a rolling angle of water droplets on its surface of 2.9-5.8°, and has excellent oil absorption performance, an oil absorption efficiency of 11.5-13.2 times its own weight, and can be reused. The preparation method of the present invention is simple, the synthesis is green and safe, the cost is low, and it is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 This is a scanning electron microscope image of the super hydrophobic and oleophilic cellulose composite aerogel material obtained in Example 1 with SiO2 size ranging from 50 to 200 nm; Figure 2 This is a wettability test diagram of the super hydrophobic and oleophilic cellulose composite aerogel material prepared in Example 1; Figure 3 This is a scanning electron microscope image of the cellulose composite aerogel material obtained in Comparative Example 1, in which the size of SiO2 is in the range of 10 to 50 nm; Figure 4 This is a test diagram of the wettability of the cellulose composite aerogel material prepared in Comparative Example 1; Figure 5This is a scanning electron microscope image of the cellulose composite aerogel material obtained in Comparative Example 2, in which the size of SiO2 is in the range of 200 to 500 nm; Figure 6 This is a test diagram of the wettability of the cellulose composite aerogel material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0009] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0010] In view of the poor super-hydrophobicity of cellulose aerogel in the prior art, which leads to poor oil adsorption performance, especially the inability to achieve a static contact angle greater than 150° and a rolling angle less than 10°, the present invention provides a super-hydrophobic and oleophilic cellulose composite aerogel material and a preparation method thereof. The performance of the obtained cellulose composite aerogel material is regulated by the size of protrusions to achieve super-hydrophobic and oleophilic properties. The preparation process is simple, the synthesis is green and safe, the drying cost is low, and mass production is possible.
[0011] In a first aspect, the present invention provides a method for preparing a super hydrophobic and oleophilic cellulose composite aerogel material, comprising the following steps: S1, placing the cellulose wet gel in a ethyl orthosilicate hydrolyzate solution, adjusting the pH value to alkaline, and performing soaking treatment and drying treatment to obtain a SiO2-reinforced cellulose composite aerogel; S2, immersing the SiO2 reinforced cellulose composite aerogel in an alkylsiloxane solution for hydrophobic modification, and drying to obtain a super hydrophobic and oleophilic cellulose composite aerogel material.
[0012] The present invention forms a blocky SiO2-reinforced cellulose composite aerogel with cellulose aerogel as the matrix and SiO2 particles as the reinforcing phase by placing the cellulose wet gel in a ethyl orthosilicate hydrolyzate solution to ensure complete immersion, and controls the pH value during the immersion process to adjust the particle size of the SiO2 particles, and then places the cellulose wet gel in an alkylsiloxane ethanol solution for hydrophobic modification, thereby obtaining a super-hydrophobic and oleophilic cellulose composite aerogel material with a contact angle greater than 150°. The material can play a great advantage in the field of oil spill treatment, not only is the material green and safe, but also with the introduction of SiO2 spheres, the mechanical properties and thermal stability of the material are improved, and the number of times the material is reused is increased.
[0013] Preferably, in step S1, the preparation step of the cellulose wet gel comprises: dissolving cellulose with an alkaline urea aqueous solution to obtain a cellulose solution; aging the cellulose solution in an alcohol solvent to obtain a wet gel; and performing a displacement treatment on the wet gel with a displacement fluid to obtain a cellulose wet gel.
[0014] Further preferably, the alkaline urea aqueous solution comprises NaOH / urea / water solution, and the mass ratio of NaOH, urea and water is (6-8):(10-14):(78-86), more preferably 7:12:81.
[0015] Further preferably, cellulose is dissolved in an alkaline urea aqueous solution, specifically comprising: precooling the alkaline urea aqueous solution to -8 to -16 °C and storing it for 2 to 4 hours, then placing cellulose in the precooled alkaline urea aqueous solution, and stirring at -2 to -6 °C for 1 to 2 hours to obtain a cellulose solution.
[0016] More preferably, the mass ratio of the alkaline urea aqueous solution to the cellulose is 100:(3-4).
[0017] More preferably, the cellulose is straw-based cellulose prepared by a conventional acid-base two-step method; the cross-sectional size of the cellulose is 5 to 20 nm, the length is 10 to 1000 nm, and the aspect ratio is (1 to 100):1.
[0018] Further preferably, the alcohol solvent includes an ethanol solution or tert-butyl alcohol with a concentration of more than 95%; the aging conditions include: the temperature is room temperature and the time is 12h to 24h. In the present invention, the aging uses an alcohol solvent, such as ethanol or tert-butyl alcohol, which can increase the freezing rate of the cellulose hydrogel, help maintain the stable structure of the cellulose nanofibers during the freeze-drying process, and reduce the cellulose extrusion and agglomeration caused by the volume expansion effect during the freezing process, thereby increasing the porosity of the aerogel and improving the material adsorption efficiency.
[0019] Further preferably, the replacement fluid includes deionized water, ethanol solution or tert-butanol, and the wet gel is completely immersed in the replacement fluid during the replacement treatment and the replacement fluid is replaced 3 to 5 times; when the alcohol solvent and the replacement fluid are the same, such as ethanol solution or tert-butanol, aging and replacement are actually carried out simultaneously.
[0020] Preferably, in step S1, the step of preparing the ethyl orthosilicate hydrolyzate comprises: mixing ethyl orthosilicate, anhydrous ethanol and water in a mass ratio of (3-5): (6-8): (1.5-2.5), stirring for 30-60 minutes in a water bath at 30-40° C., and adjusting the pH value of the obtained mixture to 2.5-3.5 to obtain the ethyl orthosilicate hydrolyzate.
[0021] More preferably, concentrated hydrochloric acid is used to adjust the pH value of the mixed solution.
[0022] Preferably, in step S1, the pH value is adjusted to 9-11; the particle size of SiO2 in the SiO2 enhanced cellulose composite aerogel is 50-200 nm.
[0023] Preferably, in step S1, ammonia water with a mass concentration of 25-28% is used to adjust the pH value. The present invention uses a weak base to adjust the pH value to avoid excessively fast reaction leading to uneven products.
[0024] Preferably, in step S1, the soaking treatment is performed at 30-40° C. for 24-48 hours.
[0025] Preferably, in step S1, the drying treatment method includes freeze drying; freeze drying specifically includes: first quick freezing in liquid nitrogen for 3 to 6 minutes, and then vacuum freeze drying at -100 to -90°C for 40 to 50 hours.
[0026] Preferably, in step S2, the mass concentration of the alkylsiloxane solution is 0.5-1%.
[0027] Preferably, in step S2, the alkyl siloxane solution is prepared by mixing alkyl siloxane with ethanol, and the alkyl siloxane includes octadecyltrimethoxysilane or dodecyltrimethoxysilane.
[0028] Preferably, in step S2, the hydrophobic modification treatment is to completely immerse the SiO2 reinforced cellulose composite aerogel in an alkylsiloxane solution for 2 to 3 minutes.
[0029] In a second aspect, the present invention provides a super hydrophobic oleophilic cellulose composite aerogel material obtained by the above preparation method, wherein the water contact angle of the super hydrophobic oleophilic cellulose composite aerogel material is 153-160°, and the rolling angle of water droplets on its surface is 2.9-5.8°.
[0030] The main mechanism of action and advantages of the present invention: (1) The present invention uses a dissolution regeneration method in an alkaline solution system to prepare a cellulose wet gel; then, tetraethyl orthosilicate is used as a silicon source, and OH is reacted with alkali as a catalyst. - Nucleophilic attack on silicon atoms, the hydrolysis rate is greater than the condensation rate, as the hydrolysis and condensation reaction continues, the silicon-oxygen chain grows to form SiO2 spherical particles; (2) Through the Cassie-Baxter model equation, we know that the rougher the surface of the object, the more pores the coating structure contains, and the better the superhydrophobic effect. For large-diameter spheres, the particles are more sparsely dispersed on the surface of the cellulose aerogel, which has little effect on the surface roughness. For spheres with too small a diameter, the composite aerogel is close to a plane from a macroscopic perspective, and the degree of roughness is not reflected, and the improvement in the hydrophobic effect is not obvious. Therefore, the present invention uses an ammonia solution to adjust the pH value of the ethyl orthosilicate hydrolyzate in which the cellulose wet gel is soaked to an alkaline range, more preferably 9 to 11, so as to adjust the SiO2 particle size to a range of 50 to 200 nm, and the superhydrophobic performance is optimal; (3) The present invention adjusts the particle size of SiO2 on the cellulose surface by using a catalyst, obtains SiO2-enhanced cellulose composite aerogel after aging and drying, and finally hydrophobically modifies the SiO2-enhanced cellulose composite aerogel by using an alkylsiloxane, and tests the optimal particle size of SiO2 in the composite aerogel and the amount of catalyst used in the experiment. The contact angle of the composite aerogel with water is 153-160°, and the rolling angle of water droplets on its surface is 2.9-5.8°.
[0031] Therefore, the present invention provides a method for preparing a super-hydrophobic and oleophilic cellulose composite aerogel material by regulating the size of protrusions; and in addition to the pH value playing a major role in the SiO2 particle size, the amount of solvent, the amount of silicon source and the reaction temperature in the ethyl orthosilicate hydrolyzate will also have a certain impact.
[0032] The present invention is further described in detail below through specific examples.
[0033] Example 1 1) Prepare 100 g of NaOH / urea / water solution with a mass ratio of 7:12:81, precool to -12 °C and store for 2 h. Place 3 g of cellulose in the NaOH / urea / water solution and stir at a low temperature of -4 °C for 1.5 h to obtain a dissolved cellulose solution.
[0034] 2) At room temperature, the dissolved cellulose was poured into a mold, and the mold was immersed in tert-butyl alcohol (analytical purity, 99.5%) and aged for 12 hours to form a wet gel. The NaOH / urea small molecules in the wet gel were replaced with water to obtain a cellulose wet gel.
[0035] 3) Mix 100 mL of tetraethyl orthosilicate, anhydrous ethanol and water in a mass ratio of 4:7:2; stir in a water bath at 30°C for 45 minutes, add concentrated hydrochloric acid dropwise to the flask to adjust the mixture to pH=3, so that the tetraethyl orthosilicate is fully hydrolyzed. Place the cellulose wet gel in the tetraethyl orthosilicate hydrolyzate solution, then add 4 g of ammonia water (25-28 wt%), adjust the pH value to 10, soak at 35°C for 24 hours, and freeze-dry (freeze-drying method: quick-freeze in liquid nitrogen for 5 minutes, then place in a freeze dryer that has been precooled to -95°C, and freeze-dry for 48 hours at an atmospheric pressure of 4 Pa after vacuuming) to obtain a block of SiO2-reinforced cellulose composite aerogel.
[0036] 4) The SiO2-reinforced cellulose composite aerogel was completely immersed in an ethanol solution of octadecyltrimethoxysilane with a mass concentration of 0.5% for 3 minutes, and then freeze-dried to obtain a super hydrophobic and oleophilic cellulose composite aerogel material.
[0037] The microstructure of the prepared cellulose composite aerogel material was analyzed. Figure 1It can be seen that SiO2 particles are tightly bound to the surface of cellulose aerogel, with particle sizes concentrated in the range of 50-200 nm, and cellulose aerogel presents a porous structure. The wetting properties of cellulose composite aerogel were tested, and the hydrophobic angle was 158.9° (e.g. Figure 2 ), the rolling angle is 3.2°.
[0038] Comparative Example 1 The only difference from Example 1 is that in step 3), ammonia water is added to adjust the pH value to 8, and the other steps and conditions are the same as those in Example 1.
[0039] The microstructure of the prepared cellulose composite aerogel material was analyzed. Figure 3 It can be seen that SiO2 particles are tightly bound to the surface of cellulose aerogel, with particle sizes concentrated in the range of 10-50nm, and cellulose aerogel presents a porous structure. The wetting properties of cellulose composite aerogel were tested, and the hydrophobic angle was 146.4° (e.g. Figure 4 ), the rolling angle is 8.4°.
[0040] Comparative Example 2 The only difference from Example 1 is that in step 3), ammonia water is added to adjust the pH value to 12, and the other steps and conditions are the same as those in Example 1.
[0041] The microstructure of the prepared cellulose composite aerogel material was analyzed. Figure 5 It can be seen that SiO2 particles are tightly bound to the surface of cellulose aerogel, the particle size is concentrated in the range of 200-500nm, and the cellulose aerogel presents a porous structure. The wetting properties of cellulose composite aerogel were tested, and the hydrophobic angle was 132.7° (e.g. Figure 6 ), the rolling angle is 11.3°.
[0042] Example 2 1) Prepare 100 g of NaOH / urea / water solution with a mass ratio of 7:12:81, precool to -12 °C and store for 4 h. Place 4 g of cellulose in the NaOH / urea / water solution and stir at -4 °C for 1 h to obtain a dissolved cellulose solution.
[0043] 2) At room temperature, the dissolved cellulose was poured into a mold, and the mold was immersed in a tert-butyl alcohol (analytical purity, 99.5%) solution and aged for 18 hours to form a wet gel. The NaOH / urea small molecules in the wet gel were replaced with ethanol to obtain a cellulose wet gel.
[0044] 3) Mix 100 mL of tetraethyl orthosilicate, anhydrous ethanol and water in a mass ratio of 4:7:2; stir in a water bath at 30°C for 60 min, add concentrated hydrochloric acid dropwise to the flask to adjust the mixture to pH=3, and fully hydrolyze the tetraethyl orthosilicate. Place the cellulose wet gel in the tetraethyl orthosilicate hydrolyzate, then add 4 g of ammonia water (25-28 wt%), adjust the pH value to 10, soak at 40°C for 24 h, and obtain a block of SiO2-enhanced cellulose composite aerogel after freeze-drying.
[0045] 4) The SiO2-reinforced cellulose composite aerogel was completely immersed in an ethanol solution of octadecyltrimethoxysilane with a mass concentration of 0.5% for 2 minutes, and then freeze-dried to obtain a super hydrophobic and oleophilic cellulose composite aerogel material.
[0046] Example 3 1) Prepare 100 g of NaOH / urea / water solution with a mass ratio of 7:12:81, precool to -16 °C and store for 2 h. Place 4 g of cellulose in the NaOH / urea / water solution and stir at -5 °C for 1 h to obtain a dissolved cellulose solution.
[0047] 2) At room temperature, the dissolved cellulose was poured into a mold, and the mold was immersed in an ethanol solution (analytical purity, 95%) and aged for 24 hours to form a wet gel. The NaOH / urea small molecules in the wet gel were replaced with ethanol to obtain a cellulose wet gel.
[0048] 3) Mix 100 mL of tetraethyl orthosilicate, anhydrous ethanol and water in a mass ratio of 4:7:2; stir in a water bath at 40°C for 30 min, add concentrated hydrochloric acid dropwise to the flask to adjust the mixture to pH=3, so that the tetraethyl orthosilicate is fully hydrolyzed. Place the cellulose wet gel in the tetraethyl orthosilicate hydrolyzate, then add ammonia water to adjust the pH value to 10, soak at 30°C for 48 h, and obtain a block of SiO2-reinforced cellulose composite aerogel after freeze-drying.
[0049] 4) The SiO2-reinforced cellulose composite aerogel was completely immersed in a 1% mass concentration of octadecyltrimethoxysilane ethanol solution for 3 minutes, and then freeze-dried to obtain a super hydrophobic and oleophilic cellulose composite aerogel material.
[0050] Example 4 1) Prepare 100 g of NaOH / urea / water solution with a mass ratio of 7:12:81, precool to -16 °C and store for 2 h. Place 4 g of cellulose in the NaOH / urea / water solution and stir at a low temperature of -2 °C for 2 h to obtain a dissolved cellulose solution.
[0051] 2) At room temperature, the dissolved cellulose was poured into a mold, and the mold was immersed in an ethanol solution (analytical purity, 95%) and aged for 18 hours to form a wet gel. The NaOH / urea small molecules in the wet gel were replaced with water to obtain a cellulose wet gel.
[0052] 3) Mix 100 mL of tetraethyl orthosilicate, anhydrous ethanol and water in a mass ratio of 5:8:2; stir in a water bath at 30°C for 40 min, add concentrated hydrochloric acid dropwise to the flask to adjust the mixture to pH=3, so that the tetraethyl orthosilicate is fully hydrolyzed. Place the cellulose wet gel in the tetraethyl orthosilicate hydrolyzate, then add ammonia water to adjust the pH value to 10, soak at 35°C for 36 h, and obtain a block of SiO2-reinforced cellulose composite aerogel after freeze-drying.
[0053] 4) The SiO2-reinforced cellulose composite aerogel was completely immersed in an ethanol solution of octadecyltrimethoxysilane with a mass concentration of 0.8% for 3 minutes, and then freeze-dried to obtain a super hydrophobic and oleophilic cellulose composite aerogel material.
[0054] The pump oil adsorption rate and wetting performance of the super hydrophobic oleophilic cellulose composite aerogel material prepared in Examples 1-4 were tested. Specifically, the super hydrophobic oleophilic cellulose composite aerogel material was placed on a water surface to which pump oil (methylene blue dyed) was dripped. It was found that the pump oil adsorption was quickly completed. When there was no obvious reduction in the pump oil and the weight of the aerogel material basically no longer increased, it was considered to be adsorbed saturated. The aerogel material was taken out and the adsorption efficiency was calculated. The super hydrophobic oleophilic cellulose composite aerogel material of the present invention extremely repels water and does not absorb water at all under a short period of low water pressure. Therefore, the adsorption efficiency = (mass after absorption saturation - initial mass) / initial mass. The results are shown in Table 1 below.
[0055] Table 1 Pump oil adsorption rate and wettability of aerogel materials obtained in Examples 1-4
[0056] As shown in Table 1, the cellulose composite aerogel material prepared by the present invention has good hydrophobicity, its contact angle with water is 153-160°, and the rolling angle of water droplets on its surface is 2.9-5.8°. The oil absorption efficiency is 11.5-13.2 times of its own weight, and the oil absorption capacity is strong.
[0057] The super hydrophobic oleophilic cellulose composite aerogel material prepared in Example 2 was tested for cyclic oil absorption efficiency and hydrophobic angle. Specifically, the super hydrophobic oleophilic cellulose composite aerogel material was placed on a water surface with a drop of pump oil (dyed with methylene blue) for adsorption. After the first adsorption was completed, it was squeezed out and then tested again. The specific test results are shown in Table 2.
[0058] Table 2 Cyclic test results of Example 2
[0059] As shown in Table 2, in the first oil absorption test, the super hydrophobic oleophilic cellulose composite aerogel material has an adsorption rate of up to 12.3 g / g for pump oil, a hydrophobic angle of 157.6°, and a rolling angle of 3.8°. When repeated for the fifth time, the pump oil adsorption rate is still 7.5 g / g, the hydrophobic angle is 142.5°, and the rolling angle is 10.5°. After being reused 5 times, it can still maintain an oil absorption efficiency of 7.5 times, thereby reflecting the reusability of the material obtained by the present invention. This is because the super hydrophobic oleophilic cellulose composite aerogel material has a large number of macropores and mesopores inside it. These pores of different levels provide diffusion channels (macropores) and oil storage spaces (mesopores) for adsorbing oil stains. At the same time, SiO2 on the cellulose surface improves the hydrophobicity and mechanical properties of the cellulose aerogel, so it can quickly absorb oil and reduce the destructiveness of the composite aerogel.
[0060] Different from the prior art, the present invention provides a super-hydrophobic and oleophilic cellulose composite aerogel material and a preparation method thereof. The aerogel material prepares a cellulose wet gel by a dissolution regeneration method in an alkali system. Under the condition of an alkali as a catalyst, the hydrolysis-polycondensation rate of tetraethyl orthosilicate (TEOS) is controlled to regulate the size of the generated SiO2 particle size, and in this process, the cellulose and SiO2 are composited. Block SiO2-reinforced cellulose composite aerogel is obtained by freeze-drying. The SiO2-reinforced cellulose composite aerogel is hydrophobically modified with alkyl siloxane to obtain a super-hydrophobic and oleophilic cellulose composite aerogel material. The super-hydrophobic and oleophilic cellulose composite aerogel has a contact angle with water of 153 to 160°, a rolling angle of water droplets on its surface of 2.9 to 5.8°, and has excellent oil absorption performance. In view of the defect that the existing cellulose aerogel fails to achieve super-hydrophobic performance, the present invention achieves the super-hydrophobic effect of the final composite aerogel by adjusting the protrusion size of the SiO2 reinforcement phase in the composite aerogel and improving the surface roughness of the composite aerogel. At the same time, the addition of SiO2 improves the mechanical properties of the composite aerogel, so that the super-hydrophobic and oleophilic cellulose composite aerogel of the present invention can be reused.
[0061] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a super hydrophobic and oleophilic cellulose composite aerogel material, characterized in that: The following steps are involved: S1, placing the cellulose wet gel in a ethyl orthosilicate hydrolyzate solution, adjusting the pH value to alkaline, and performing soaking treatment and drying treatment to obtain a SiO2-reinforced cellulose composite aerogel; S2, immersing the SiO2 reinforced cellulose composite aerogel in an alkylsiloxane solution for hydrophobic modification, and drying to obtain a super hydrophobic and oleophilic cellulose composite aerogel material.
2. The method for preparing the super hydrophobic and oleophilic cellulose composite aerogel material according to claim 1, characterized in that: In step S1, the preparation steps of the cellulose wet gel include: dissolving cellulose with an alkaline urea aqueous solution to obtain a cellulose solution; aging the cellulose solution in an alcohol solvent to obtain a wet gel; and performing a displacement treatment on the wet gel with a displacement fluid to obtain a cellulose wet gel.
3. The method for preparing the super hydrophobic and oleophilic cellulose composite aerogel material according to claim 2, characterized in that: The alkaline urea aqueous solution comprises NaOH / urea / water solution, and the mass ratio of NaOH, urea and water is (6-8): (10-14): (78-86); The preparation of the cellulose solution specifically includes: precooling the alkaline urea aqueous solution to -8 to -16 °C and storing it for 2 to 4 hours, then placing cellulose in the precooled alkaline urea aqueous solution, and stirring it at -2 to -6 °C for 1 to 2 hours to obtain a cellulose solution; The mass ratio of the alkaline urea aqueous solution to the cellulose is 100:(3-4); The cross-sectional size of the cellulose is 5 to 20 nm, the length is 10 to 1000 nm, and the aspect ratio is (1 to 100):
1.
4. The method for preparing the super hydrophobic and oleophilic cellulose composite aerogel material according to claim 2, characterized in that: The alcohol solvent includes an ethanol solution or tert-butyl alcohol with a concentration of more than 95%; The aging conditions include: the temperature is room temperature, the time is 12h to 24h; The replacement fluid includes deionized water or ethanol.
5. The method for preparing the super hydrophobic and oleophilic cellulose composite aerogel material according to claim 1, characterized in that: In step S1, the preparation step of the tetraethyl orthosilicate hydrolyzate includes: mixing tetraethyl orthosilicate, anhydrous ethanol and water in a mass ratio of (3-5): (6-8): (1.5-2.5), stirring for 30-60 min in a water bath at 30-40° C., and then adjusting the pH value of the obtained mixed solution to 2.5-3.5 to obtain the tetraethyl orthosilicate hydrolyzate.
6. The method for preparing the super hydrophobic and oleophilic cellulose composite aerogel material according to claim 1, characterized in that: In step S1, ammonia water is used to adjust the pH value to 9-11; The particle size of SiO2 in the SiO2-enhanced cellulose composite aerogel is 50 to 200 nm; The soaking treatment is performed at 30-40° C. for 24-48 hours; The drying method includes freeze drying.
7. The method for preparing the super hydrophobic and oleophilic cellulose composite aerogel material according to claim 1, characterized in that: In step S2, the mass concentration of the alkylsiloxane solution is 0.5-1%.
8. The method for preparing the super hydrophobic and oleophilic cellulose composite aerogel material according to claim 1, characterized in that: In step S2, the alkyl siloxane solution is prepared by mixing alkyl siloxane and ethanol, and the alkyl siloxane includes octadecyltrimethoxysilane or dodecyltrimethoxysilane.
9. The method for preparing the super hydrophobic and oleophilic cellulose composite aerogel material according to claim 1, characterized in that: In step S2, the hydrophobic modification treatment is to completely immerse the SiO2 reinforced cellulose composite aerogel in an alkylsiloxane solution for 2 to 3 minutes.
10. The super hydrophobic and oleophilic cellulose composite aerogel material prepared by the preparation method according to any one of claims 1 to 9.